2022
DOI: 10.3389/fnut.2022.918944
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based diets and body composition in Chinese omnivorous children aged 6–9 years old: A cross-sectional study

Abstract: Evidence suggests that plant-based diets are beneficial for alleviating metabolic diseases. Childhood is a crucial period for body growth and development. However, it is unknown whether adherence to a plant-based diet is related to a healthy body composition in children. We aimed to assess the relationship between a plant-based diet and body composition in children. A total of 452 Chinese children aged 6–9 years old participated in this cross-sectional study. Lean mass (LM), fat mass, and fat mass percentage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…These changes may be explained by the significant increase in physical activity and the accompanying increase in skeletal muscle mass over 3 years old. In the present study, PBF in girls were higher than that in boys in every age group, except for the 9- and 10-years old groups (all P < 0.05), which was in line with F F Chen’s results conducted in seven cities of China [ 30 ]. PBF and FMI increase rapidly again in girls aged 7–9 years, which is closely associated with the onset of puberty.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These changes may be explained by the significant increase in physical activity and the accompanying increase in skeletal muscle mass over 3 years old. In the present study, PBF in girls were higher than that in boys in every age group, except for the 9- and 10-years old groups (all P < 0.05), which was in line with F F Chen’s results conducted in seven cities of China [ 30 ]. PBF and FMI increase rapidly again in girls aged 7–9 years, which is closely associated with the onset of puberty.…”
Section: Discussionsupporting
confidence: 91%
“…The changes in body composition of boys aged 9–17 years were previously assessed using DXA in a study conducted in Colombia, where it was shown that FMI continues to decrease at this age. F F Chen [ 30 ] also reported FMI decreased obviously between 10-15 years old in boys. Unlike the age group and change characteristics from the above researches, in the present study, the FMI of boys continues to decline at the age of 11–14, subsequently increased transiently at 14–15 years old and then decreased rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The food group intakes accounted for in these nutrient intakes show that participants who have higher oPDI have higher intakes of fruits, vegetables, nuts, seeds, and legumes, and lower intakes of dairy and meat. The majority of PDI studies have been conducted in adults and focus on health outcomes; however, Chen et al studied children aged 6-9 years living in China [31]. Their food group results show that participants with higher overall plant intake have higher intakes of healthy plant foods and also some less healthy plant foods, although statistical comparisons are not completed and nutrient intakes are not reported [31].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PDI studies have been conducted in adults and focus on health outcomes; however, Chen et al studied children aged 6-9 years living in China [31]. Their food group results show that participants with higher overall plant intake have higher intakes of healthy plant foods and also some less healthy plant foods, although statistical comparisons are not completed and nutrient intakes are not reported [31]. Other PDI studies that have examined nutrient intakes report higher PDI scores in relation to higher intakes of carbohydrates [32,33], polyunsaturated fat [33], dietary fiber and vitamin B 6 [32,33], folate [32], vitamin C [33,34], and magnesium [32,33], and lower intakes of protein [15,21,33,34], total fat [15,33,34], saturated fat [15,33,34], cholesterol, vitamin B 6 , vitamin B 12 , calcium, and magnesium [15,33], although all of these studies were conducted in Iranian adults, except for one that was in South Korean adults [21].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the prevalence of AIS is higher in female than male and men's lean mass is higher than women's in both AIS patients and healthy people [31,32], we assumed sex as one source of the heterogeneity. And the result of female subgroup meta analysis showed the mean difference of lean mass between AIS patients and control group in this subgroup analysis was greater than the meta analysis, and the heterogeneity decreased in this subgroup.…”
Section: Discussionmentioning
confidence: 99%